Effect of chitosan on physicochemical and rheological attributes of bread. (April 2019) - Ghoshal, Gargi; Mehta, Sapna
The aim of this study was to develop fiber-enriched functional bread containing selected concentration of chitosan (0.1%, 0.5%, 1%, 1.5%, and 2% w/w). Dynamic rheology of bread dough established that viscous moduli were lower than elastic moduli. Until 1% chitosan concentration, dough extensibility increased. Avrami nonlinear regression equation was selected as a convenient mathematical tool to model bread crumb staling kinetics. Scanning electron microscopy, Fourier-transform infrared, differential scanning calorimetry, and extensibility tests were used to examine the changes of the structure of control dough and chitosan containing dough. Specific volume of bread was inversely proportional to firmness of bread. Firmness is directly proportional function of storage time and chitosan quantity. Sensory evaluation revealed that 1% chitosan can be used as potential functional ingredient to prevent chronic diseases like obesity, type 2 diabetes, constipation, and colon cancer.